Implementasi Metode COCOMO II untuk Estimasi Biaya Pengembangan Perangkat Lunak di CV. Profile Image Studio - Amru Nizar Maqdum; Andi Reza Perdanakusuma; Widhy Hayuhardhika Nugraha Putra (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Software cost estimation is an important aspect of an software project for budgeting. In the process of determining the price of a system in CV. The Profile Image Studio does not have specific estimation. because of that make often the company receive losses both financially and time. Based on this case, the cost estimation in this study will implement COCOMO II (Constructive Cost Mode IIl) method is implemented in calculating software costs suggestion for CV. Profile Image Studio. Cost estimates can be obtained after obtaining estimated effort, number of human resources and estimated system development time. COCOMO II (Constructive Cost Model) method is implemented in 2 systems that have been developed by CV. Studio Profile Image. At the end of this study, the cost comparison of system development was done by comparing estimated cost results obtained using the COCOMO II (Constructive Cost Model) with the allocation of costs by CV. Studio Profile Image. The results of applying the COCOMO II (Constructive Cost Model II) method in calculating software costs, it was found that the total estimated cost of the DBA ticket system was Rp.61.344.000 carried out by 3 people in 9 month while pintu air system was Rp.36.352.000 carried out by 2 people in 8 month. Difference in estimated cost for all software is 37,24% with time difference is 52,94 and people difference is 40%. So the COCOMO II method will be more precise in estimating cost of a project that can be minimize the losses received by the company.